Effect of 940 nm Diode Laser Irradiation and Dentin Bonding Agent on Permeability of Furcation Area in Primary Molars - Mohammad Atif; Nitesh Tewari; Vijay P. Mathur; Kalpana Bansal; Morankar Rahul (Indian Journal of Dental Research)
Purpose: Multiple accessory canals make furcation area of primary molars the most common port of entry of bacterial endotoxins to periradicular area. Reduction in permeability can improve prognosis of these teeth. Therefore, this study was designed to compare the effect of 940 nm diode laser and dentin bonding agent on the dye penetration of furcation area in primary molars. Material and Methods: Thirty teeth were divided into three groups, that is, Group 1 (control group), Group 2 (dentin bonding agent applied over floor of pulp chamber), and Group 3 (diode laser irradiated over floor of pulp chamber). The samples were prepared and seven from each group were tested by dye penetration and three were sent for scanning electron microscopy. Rise in temperature in the perifurcal area was also recorded at the time of laser irradiation. Dunn’s pair-wise comparison analysis was used for the analysis for the difference in dye penetration among the group. Results: The maximum rise in temperature recorded postirradiation was 6.90C. Dye penetration was significantly reduced in Group 2 Dentin bonding group (DBG) as compared to control group (P = 0.0025). Reduction in permeability was observed in Group 3 Laser group (LG) but this was not statistically significant (P = 0.197). Scanning electron microscope revealed open dentinal tubules in Group 1. There were no open dentinal tubules in Group 2, while Group 3 had sealed dentinal tubules with glass-like surface over the region. Conclusion: Dentin bonding agent led to substantial decrease in dye penetration of furcation area of primary molars. This method should be evaluated clinically to improve successful pulpectomy procedures of primary molars.